Real-world use of imipenem/cilastatin/relebactam for the treatment of KPC-producing Klebsiella pneumoniae complex and difficult-to-treat resistance (DTR) Pseudomonas aeruginosa infections: a single-center preliminary experience - Leanza, Cristiana; Mascellino, Maria Teresa; Volpicelli, Lorenzo; Covino, Sara; Falletta, Antonio; Cancelli, Francesca; Franchi, Cristiana; Carnevalini, Martina; Mastroianni, Claudio M.; Oliva, Alessandra (Frontiers in Microbiology, 2024)
Introduction Real-life experience with imipenem/cilastatin/relebactam (IMI/REL) for the treatment of KPC-producing Klebsiella pneumoniae complex (KPC-Kp) and difficult-to-treat resistance (DTR) Pseudomonas aeruginosa (DTR-PA) infections is herein described. Methods Adult patients with KPC-Kp or DTR-PA infections who received ≥48 h of IMI/REL were included. Clinical and microbiological outcomes were retrieved through the medical records. Primary outcome was clinical cure. Secondary outcomes included mortality from infection onset and adverse effects attributable to IMI/REL. Results We included 10 patients with different infections caused by DTR-PA (n = 4), KPC-Kp [n = 5, of which 3 ceftazidime/avibactam-resistant (CTV-R KPC-Kp), 2 CTV susceptible (CTV-S KPC-Kp)] or both DTR-PA/KPC-Kp (n = 1) successfully treated with IMI/REL: 3 hospital-acquired pneumonia, 1 ventilator-associated pneumonia, 2 skin and soft tissue infections, 1 osteomyelitis, 2 bloodstream infections, 1 complicated urinary tract infection. Clinical cure was achieved in all cases. No patients died and no side effect were reported. Discussion We reported the preliminary real-life experience on the successful and safe use of IMI/REL for the treatment of KPC-Kp or DTR-PA complicated infections, including pneumonia and bone infections.